1998
DOI: 10.1111/j.1460-9568.1998.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐localized neuropeptide Y and GABA have complementary presynaptic effects on sensory synaptic transmission

Abstract: We have examined the morphological relationship of neuropeptide Y (NPY) and GABAergic neurons in the lamprey spinal cord, and the physiological effects of NPY and GABA(B) receptor agonists on afferent synaptic transmission. NPY-containing fibres and cell bodies were identified in the dorsal root entry zone. NPY immunoreactive (-ir) fibres made close appositions with primary afferent axons. Co-localization of NPY and GABA-ir was found in the dorsal horn and dorsal column. Fifty-two per cent of NPY-ir profiles s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 55 publications
4
36
0
Order By: Relevance
“…The CNS expression of the lamprey receptor, along with earlier studies revealing high expression levels of NPY and PYY in the lamprey CNS [4], clearly motivates further investigation of the possible neuronal functions of the lamprey receptor. The previous description of NPY effects in the lamprey spinal cord [29] encourages studies of the receptor in this context. The expression pattern also suggests that the lamprey receptor could have a role in peripheral functions of the NPY-family peptides, such as regulation of gastrointestinal tract endocrine functions and blood pressure.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The CNS expression of the lamprey receptor, along with earlier studies revealing high expression levels of NPY and PYY in the lamprey CNS [4], clearly motivates further investigation of the possible neuronal functions of the lamprey receptor. The previous description of NPY effects in the lamprey spinal cord [29] encourages studies of the receptor in this context. The expression pattern also suggests that the lamprey receptor could have a role in peripheral functions of the NPY-family peptides, such as regulation of gastrointestinal tract endocrine functions and blood pressure.…”
Section: Discussionmentioning
confidence: 76%
“…Porcine NPY, p[Leu31,Pro34]NPY, the series of amino terminally truncated pig NPY peptides pNPY , pNPY 13236 , pNPY [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] , pNPY [25][26][27][28][29][30][31][32][33][34][35][36] , pNPY [26][27][28][29][30][31][32][33][34][35][36] , and bovine PP were from Bachem (King of Prussia, PA, USA); p[D-Trp32]NPY was from Peninsula Laboratories Inc. Lamprey peptides were synthesized as described below. BIBP3226 was kindly provided by K. Thomae GmBH, Biberach, Germany.…”
Section: Peptides and Nonpeptidic Antagonistsmentioning
confidence: 99%
“…This indicates that Hcrt is capable of acting presynaptically by increasing the release of neurotransmitter, putatively glutamate, from a population of axon terminals that impinge on spinal motoneurons John et al, 2003;Peever et al, 2003). In favor of a postsynaptic action of Hcrt, (1) applied Hcrt produced large-amplitude, long-lasting membrane depolarization, which would not be expected if the mechanism of action were purely presynaptic (Del Negro and Chandler, 1998;Parker et al, 1998), and (2) preliminary anatomical data indicate that Hcrt-containing fibers are apposed to lumbar motoneurons and that these cells contain Hcrt membrane receptors . A physiological postsynaptic effect induced by Hcrt is peculiar, because most peptides are colocalized with and act to alter the release of classic neurotransmitters (Lohof et al, 1993;Li et al, 1998).…”
Section: Mode Of Action Of Hcrt On Motoneuronsmentioning
confidence: 99%
“…In the lamprey spinal cord, N PY-immunoreactive axons (many of which also contain GABA) form close associations with primary afferents (Bongianni et al, 1990). Parker et al (1998) have recently demonstrated that N PY not only acted presynaptically to reduce the amplitude of primary afferentevoked EPSPs on spinobulbar neurons but also decreased the excitability of these neurons, which was thought to be a postsynaptic action. Spinobulbar neurons in the lamprey appear to be homologous with spinothalamic neurons in mammals, and some of the lamina III / IV N K1 receptor-immunoreactive neurons in the rat belong to this tract (Marshall et al, 1996).…”
Section: Npy Receptorsmentioning
confidence: 99%